2018
DOI: 10.1073/pnas.1716016115
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-dependent epigenetic regulation of soluble epoxide hydrolase via DNA methylation

Abstract: To elucidate molecular mechanisms responsible for the sexually dimorphic phenotype of soluble epoxide hydrolase (sEH) expression, we tested the hypothesis that female-specific down-regulation of sEH expression is driven by estrogen-dependent methylation of the gene. Mesenteric arteries isolated from male, female, ovariectomized female (OV), and OV with estrogen replacement (OVE) mice, as well as the human cell line (HEK293T) were used. Methylation-specific PCR and bisulfite genomic sequencing analysis indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…As noted above, such effects are unlikely to play a major role for the developmental trajectories observed in this study. Normally, preterm pigs delivered at or slightly before 90% gestation (0.6 -1.1 kg birth wt) show variable degrees of respiratory distress, reduced systemic immunity, and high NEC sensitivity, especially when fed rapidly increasing amounts of infant formulas (46,51,53). These symptoms were generally absent for the present moderately preterm pigs (1.1 kg at birth), in part because we fed gradually increasing volumes of bovine colostrum, which protects preterm pigs against NEC and sepsis (10,49), followed by a slow transition to mature bovine milk and without use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, such effects are unlikely to play a major role for the developmental trajectories observed in this study. Normally, preterm pigs delivered at or slightly before 90% gestation (0.6 -1.1 kg birth wt) show variable degrees of respiratory distress, reduced systemic immunity, and high NEC sensitivity, especially when fed rapidly increasing amounts of infant formulas (46,51,53). These symptoms were generally absent for the present moderately preterm pigs (1.1 kg at birth), in part because we fed gradually increasing volumes of bovine colostrum, which protects preterm pigs against NEC and sepsis (10,49), followed by a slow transition to mature bovine milk and without use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in DNA/CG methylation of EPHX2 , a pattern dependent on estrogens and which is found more frequently in females, is associated with reduced promoter activity. Thus, oestrogens decrease sEH mRNA and protein abundance and DNA methyltransferase inhibitors increase its expression . Chromatin immunoprecipitation experiments revealed that binding of the transcription factors SP‐1, AP‐1 and NF‐κB to the promoter of EPHX2 is reduced in female mice and human cells after treatment with 17ß‐estradiol .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oestrogens decrease sEH mRNA and protein abundance and DNA methyltransferase inhibitors increase its expression . Chromatin immunoprecipitation experiments revealed that binding of the transcription factors SP‐1, AP‐1 and NF‐κB to the promoter of EPHX2 is reduced in female mice and human cells after treatment with 17ß‐estradiol . The role of histone modifications in this context is, however, unknown so far.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 2ME inhibits CYP1B1 activity and reduces HETE formation and cardiac remodeling in rats with pressure overload-induced cardiac hypertrophy [114]. Moreover, E2 inhibits the expression/activity of soluble epoxide hydrolase (sEH), a key enzyme in EET metabolism [144]. Several studies linked low sEH activity to the pathophysiology of PAH: (1) E2-, genetic-, and pharmacologically-induced downregulation of sEH (and increased pulmonary EET) potentiates hypoxic pulmonary vasoconstriction [145][146][147]; (2) lungs from PH patients express no/little sEH; (3) hypoxia decreases the expression of sEH; and (4) when exposed to hypoxia, sEH KO mice exhibit exacerbated pulmonary vascular remodeling [147].…”
Section: Role Of Cyp1b1 and Estrogens In Arachidonic Acid Metabolismmentioning
confidence: 99%